التوافقيات العليا وأثرها على استقرار عمل الآلة التحريضية - حسين سوزي (Latakia University Journal -Engineering Sciences Series, 2017)
يقدم البحث فكرة هامة عن التوافقيات العليا (الفراغية والزمنية) وما هو سبب ظهورها وآثارها السلبية على مستهلكات الطاقة الكهربائية. تم حساب العزوم الدوارة المتولدة عن التوافقيات العليا وأثرها على المميزة الميكانيكية للمحرك التحريضي، وكيف يمكن أن نخفف من هذا الأثر بالطريقة التصميمية للمحرك. ينتج عن التوافقيات العليا مفاقيد كهربائية ومغناطيسية إضافية في المحرك التحريضي تؤدي إلى زيادة تسخين المحرك وانخفاض المردود ومعامل الاستطاعة. لقد بين البحث كيف يمكن التخفيف من هذه المفاقيد وبالتالي تحسين شكل المميزة الميكانيكية للمحرك التحريضي وتحسين أداءه أيضاً. This paper presents an important idea about the higher harmonics (both temporal and spatial) and the reason of their appearance and negative effects they cause on the electrical power consumers. Generated rotating torques from upper harmonics is then calculated, and their effect on the mechanical characteristics of the induction motor, and how to mitigate this effect depending on motor design. Higher harmonics produce additional electrical and magnetic losses in induction motors which increase the motor’s heat and decrease its energy yield and power coefficient. This research shows how to decrease these losses to improve the mechanical characteristics of the induction motor and enhance the performance.